2017
DOI: 10.3390/rs9010085
|View full text |Cite
|
Sign up to set email alerts
|

Remote Sensing-Based Assessment of the 2005–2011 Bamboo Reproductive Event in the Arakan Mountain Range and Its Relation with Wildfires

Abstract: Pulse ecological events have major impacts on regional and global biogeochemical cycles, potentially inducing a vast set of cascading ecological effects. This study analyzes the widespread reproductive event of bamboo (Melocanna baccifera) that occurred in the Arakan Mountains (Southeast Asia) from 2005 to 2011, and investigates the possible relationship between massive fuel loading due to bamboo synchronous mortality over large areas and wildfire regime. Multiple remote sensing data products are used to map t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…Similarly to our results for white spruce, in these studies the same climate cue (precipitation in previous months) was responsible for both the induction of flowering and the increase of burnt area, due to fuel build‐up and improved fuel connectivity after moist years. A significant increase in burnt area has also been observed after widespread reproduction of bamboo in South‐East Asia (Fava & Colombo, ), although in this case fire is not driven by weather, but rather by the increase in fuel that followed post‐reproduction mortality of bamboo over large areas.…”
Section: Discussionmentioning
confidence: 97%
“…Similarly to our results for white spruce, in these studies the same climate cue (precipitation in previous months) was responsible for both the induction of flowering and the increase of burnt area, due to fuel build‐up and improved fuel connectivity after moist years. A significant increase in burnt area has also been observed after widespread reproduction of bamboo in South‐East Asia (Fava & Colombo, ), although in this case fire is not driven by weather, but rather by the increase in fuel that followed post‐reproduction mortality of bamboo over large areas.…”
Section: Discussionmentioning
confidence: 97%
“…Indeed, it has been observed that, especially in the dry years, recently dead bamboo forests catch fire more easily than actively growing bamboo forests do (Dalagnol et al 2018). Also, a study on Melocanna baccifera bamboo forests in Myanmar showed that, after a die-off event, the burned areas in bamboo forests more or less doubled (Fava and Colombo 2017). Adding human disturbance to increased flammability easily leads to wildfires as seen in the more southern parts of Amazonia (Cochrane and Laurance 2008;Devisscher et al 2016).…”
Section: The Possibility Of Passing a Threshold Between Forest And Samentioning
confidence: 99%
“…For normal distribution, the average and standard deviation were computed. For skewed distribution, a more appropriate method was applied to estimate the average, standard deviation and skewness parameter (xi) (Fernandez and Steel, 1998).…”
Section: Tree Cover Productmentioning
confidence: 99%
“…Since areas with dead bamboo are difficult to maintain trails and hinder the work of rubber trappers (Carvalho et al, 2013), it can be used in forest management planning in order to avoid areas where the die-off year occurred in the last 3 years and dry culms are still not decomposed, or to avoid areas with likely future die-off. It can also be used for public policy planning regarding food and human health security, for example, in bamboo forests in Southeast Asia, where bamboo reproductive events cause huge rodent invasion and proliferation that then damage nearby crop plantations (Fava and Colombo, 2017). It could also be used to explore broader scientific questions on the ecology of bamboo-dominated forests such as studies on maintenance/expansion of bamboo patches, flowering waves, cross-pollination between patches, fauna habitat dynamics and impacts on short-and long-term carbon dynamics.…”
Section: Bamboo Die-off Predictionmentioning
confidence: 99%